2012
DOI: 10.1007/s00449-012-0685-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of biological sulfide removal in a CSTR bioreactor

Abstract: In this study, biological sulfide removal from natural gas in a continuous bioreactor is investigated for estimation of the optimal operational parameters. According to the carried out reactions, sulfide can be converted to elemental sulfur, sulfate, thiosulfate, and polysulfide, of which elemental sulfur is the desired product. A mathematical model is developed and was used for investigation of the effect of various parameters on elemental sulfur selectivity. The results of the simulation show that elemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
1
0
2
Order By: Relevance
“…For example, Lohwacharin and Annachhatre reported an oxidation selectivity to sulfur of up to 90% in an aerobic gas-lift bioreactor. Similar values were obtained by Roosta et al in which a sulfur production of 87.8% was obtained using a model validated with an aerobic CSTBR. Our results are in good agreement with other studies conducted in anoxic BTFs.…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, Lohwacharin and Annachhatre reported an oxidation selectivity to sulfur of up to 90% in an aerobic gas-lift bioreactor. Similar values were obtained by Roosta et al in which a sulfur production of 87.8% was obtained using a model validated with an aerobic CSTBR. Our results are in good agreement with other studies conducted in anoxic BTFs.…”
Section: Results and Discussionsupporting
confidence: 89%
“…Also, Fajardo et al found a higher maximum autotrophic denitrifying activity at a pH value of 8 than at 7 for a bacterial consortium using H 2 S as an electron donor. However, as reported by Roosta et al, working at high pH values decreases the sulfur selectivity (because of the promotion of its oxidation to sulfate and increase in polysulfide concentration), highlighting a possible limitation to bear in mind.…”
Section: Results and Discussionmentioning
confidence: 83%
“…Diseño, caracterización y aplicación de microelectrodos para el estudio de biopelículas sulfuroxidantes biopelícula cultivada en el BPP-FG se describió utilizando las correlaciones desarrolladas en el capítulo 7 (Ecuación 7.15 y Ecuación 7.22). De este modo, la principal incertidumbre es la descripción de la cinética de degradación de H 2 S. La cinética de degradación del H 2 S se modelizó considerando que la eliminación del H 2 S tiene lugar en dos etapas (Mannucci et al 2012;Rodriguez 2013;Roosta et al 2012):…”
Section: Sulfuroxidanteunclassified
“…Por este motivo, es difícil comparar los resultados presentados en estos trabajos con los obtenidos en el estudio actual. Sin embargo, en Roosta et al (2012) diferencian entre el consumo de oxígeno máximo para la oxidación de las 2 especies (sulfuro y azufre elemental). El valore reportado en este trabajo (0.093 mg OD•g SSV -1 •s -1 para la primera reacción y 0.14 mg OD•g SSV -1 •s -1 para la segunda reacción) es un orden de magnitud mayor al presentado en el trabajo actual.…”
Section: Sección Reactor Qmaxb1unclassified